The influence of the body weight increase on the VO2max and anaerobic capacity decrease of firemen in 5 years - Cesar Henrique Dalquano; Nelson Nardo Júnior; Ane Beatriz Dalquano (Revista da Educação Física)
The present study aimed to verify the influence of the aging process, as well as of the weight gain on the VO2max and the anaerobic capacity of firemen of Maringá, in the current age group of 31 to 40 years. That population is of special interest for verifying the chronic effect of physical activities regular, because the same ones maintain a routine that includes aerobic and anaerobic exercises, 3 times a week with duration of 60 minutes and present superior conditioning levels when compared with the majority of the population of the same age group. Cooper’s 12-minute test and Matsudo’s 40-second test were used to measure aerobic and anaerobic capacities. The body weight and height were also collected. These tests were applied to a sample of 40 men in 1995 and reapplied to 37 of the 40 men in 2000. The results 12-minute and of 40-second tests showed that the physical activity helps to maintain the level of physical aptitude. When the sample was divided in two groups: G1 (increase > 5kg n=12) and G2 (increase < 5kg n=25), and compared between themselves (results of 1995 x 2000) a significant reduction was verified (p < 0,05) in the VO2max and in the anaerobic capacity of group G1, while G2 presented no significant difference in this period. These results indicate that the increase in corporal mass in aging people is an important factor in the decline of the appraised functions and the regular physical activity helps to maintain, within a certain limit, the physiologic functions with the passing of time.